2016 IEEE/ION Position, Location and Navigation Symposium (PLANS) 2016
DOI: 10.1109/plans.2016.7479707
|View full text |Cite
|
Sign up to set email alerts
|

On the feasibility of cm-accurate positioning via a smartphone's antenna and GNSS chip

Abstract: Abstract-The feasibility of centimeter-accurate carrier-phase differential GNSS (CDGNSS) positioning using a smartphone's internal GNSS antenna and GNSS chip is investigated. Precise positioning on a mass-market platform would significantly influence the world economy, ushering in a host of consumer-focused applications that have so far been hampered by the several-meter-level errors in traditional GNSS positioning. Previous work has shown that GNSS signals received through a mass-market smartphone's GNSS ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 9 publications
4
49
0
2
Order By: Relevance
“…They showed that smartphone measurements were noisy and suffered from a significant number of outliers in comparison with those collected by a U-Blox low-cost receiver and achieved only a meter-level positioning. In 2016, Humphreys et al [3] were able to access GNSS raw measurements collected by a modified Samsung Galaxy S5 smartphone equipped with a Broadcom GNSS chipset running a customized Android Marshmallow (provided by Broadcom) including a modified GPS library that recorded RINEX (Receiver Independent Exchange Format) files to the phone's storage card. Their analysis revealed that under typical smartphone use, the effects of local multipath was the main drawback to achieving a centimeter-accurate smartphone positioning.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that smartphone measurements were noisy and suffered from a significant number of outliers in comparison with those collected by a U-Blox low-cost receiver and achieved only a meter-level positioning. In 2016, Humphreys et al [3] were able to access GNSS raw measurements collected by a modified Samsung Galaxy S5 smartphone equipped with a Broadcom GNSS chipset running a customized Android Marshmallow (provided by Broadcom) including a modified GPS library that recorded RINEX (Receiver Independent Exchange Format) files to the phone's storage card. Their analysis revealed that under typical smartphone use, the effects of local multipath was the main drawback to achieving a centimeter-accurate smartphone positioning.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with the advent of the Android Nougat operating system (version 7.x or 8.x), some smart devices allow direct access to raw data and the PVT (position velocity time) solution by acquiring pseudo ranges and carrier-phase from the chipset inside [5,6]. Many other sensors are available today on smartphones; most of them are related to internal applications (e.g., proximity sensor, light sensors), while others (e.g., inertial measurements unit and camera) can be used for estimating a positioning solution, but these aspects are out of the scope of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Under ideal scenarios, consumer-grade GNSS receivers can reach several meters of positioning accuracy, the improvement of which will further promote the diversification of LBS [1]. However, the positioning capability will decrease in some harsh conditions, such as urban canyons or short distance tunnels, where GNSS signals suffer from a low signal-to-noise ratio and severe multipath [2,3]. Multi-GNSS receiver autonomous integrity monitoring (RAIM) can reduce the large positioning errors and achieve satisfactory positioning performance in degraded-signal The phase and Doppler observations are provided directly, while the pseudorange is computed with the time of signal transmitted and received as follows:…”
Section: Introductionmentioning
confidence: 99%